Exploring the pedagogical value of ICT in life sciences teaching and learning - Lubisi, Gift Thamsanqa (University of the Witwatersrand, Johannesburg, 2024)
Life Sciences (LS) is a subject that is mostly based on theoretical and practical ideas that may be difficult to prove in a classroom context. It is thus not easy for some learners to grasp. This study therefore sought to explore the use of Information and Communication Technologies (ICTs) by six LS teachers teaching in three grades (10, 11, and 12) in two public schools located in the Gauteng province in South Africa. It sought to investigate how ICT usage enhances learner understanding of LS concepts. A qualitative research design was used for data collection and analysis. Laurillard’s media forms helped to make sense of data from semi- structured interviews and one lesson observed for each of the six teachers. The findings revealed that all participating teachers perceived the effectiveness of ICTs as enabling learners to ‘see’ LS abstract concepts. Their use of ICTs in the classroom was confined to narrative, interactive, and communicative media forms. There is evidence that suggests that the pedagogical value of the technologies is aligned with the teachers’ perceptions as the combination of the three media forms facilitates visualization of abstract concepts— depending on how they are used. Therefore, this research recommends that the use of ICTs (in this case, the smartboards and learner laptops) be extended to the utilization of the adaptive media where learners can be exposed to simulations to help them concretize their understanding of LS. My main argument and findings are that these concepts within the framework will only be effective based on how the teacher views and applies it. I also observed that if learners have access to technologies for learning the subject, potentially better (deeper) learning will be achieved through its use. Moreover, if learners are not given opportunities to apply the learning, engage in a critical way to reveal the importance of ICTs in their lives, pedagogical efforts remain futile. Thus, pedagogical value is key in ICT integration, not only in LS but in all learning.
A research report submitted in fulfillment of the requirements for the Master of Education in Educational Technology, In the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Enhancement of learning; Learning outcomes; Life Sciences; Media forms; Pedagogical value; Teaching with ICTs; SDG-4: Quality education